2021
DOI: 10.3748/wjg.v27.i19.2366
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the nutritional status of nine vitamins in patients with esophageal cancer during chemotherapy

Abstract: BACKGROUND Many studies have investigated the relationships between vitamins and esophageal cancer (EC). Most of these studies focused on the roles of vitamins in the prevention and treatment of EC, and few studies have examined the changes in vitamin nutritional status and their influencing factors before and after chemotherapy for EC. Chemotherapy may have a considerable effect on EC patients’ vitamin levels and hematological indicators. AIM To research the nutritiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…This result aligns with previous studies [ 40 42 ]. Moreover, we observed a continuous reduction in hemoglobin levels over time during chemotherapy, contrasting with findings by Movahed et al [ 25 ] and Liang et al [ 26 ]. The multi-factorial and complex mechanisms of cancer anemia, including malnutrition, make it a recognized independent prognostic factor for poor patient survival [ 43 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result aligns with previous studies [ 40 42 ]. Moreover, we observed a continuous reduction in hemoglobin levels over time during chemotherapy, contrasting with findings by Movahed et al [ 25 ] and Liang et al [ 26 ]. The multi-factorial and complex mechanisms of cancer anemia, including malnutrition, make it a recognized independent prognostic factor for poor patient survival [ 43 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study demonstrated improvements in serum albumin levels and Mini Nutritional Assessment scores in patients with malignant lymphoma after chemotherapy [ 24 ]. In contrast, Movahed et al [ 25 ] and Liang et al [ 26 ] observed significant reductions in the levels of total protein and serum albumin in esophageal cancer patients during chemotherapy. Yamano [ 27 ] reported significant decreases in BMI and serum albumin levels in rectal cancer patients during and after chemoradiotherapy, with no significant difference in prealbumin levels.…”
Section: Discussionmentioning
confidence: 93%
“…Corrections of micronutrients before surgery should be a priority because untreated micronutrient deficiencies, such as iron, thiamin, vitamin B 12 , or vitamin D deficiency, can lead to undesired postoperative complications. [59][60][61] On the other hand, some patients supplement their diet with high-dose vitamins, immunostabilizing micronutrients, and antioxidants without input from the treating physician. This can lead to concern of unwanted drug-nutrient interactions or risk of toxicity over time.…”
Section: Assessment and Diagnosismentioning
confidence: 99%
“…Micronutrient deficiencies can be screened and assessed for part of a comprehensive assessment, including biochemical data, and an NFPE. Corrections of micronutrients before surgery should be a priority because untreated micronutrient deficiencies, such as iron, thiamin, vitamin B 12 , or vitamin D deficiency, can lead to undesired postoperative complications 59–61 . On the other hand, some patients supplement their diet with high‐dose vitamins, immunostabilizing micronutrients, and antioxidants without input from the treating physician.…”
Section: Prehabilitation With a Nutrition Componentmentioning
confidence: 99%
“…It is important to recognize that metabolic and nutrition alterations can influence survival in patients who have cancer. Malnutrition often worsens during treatment and is also linked with significantly worse outcomes in treatment, with as much as a 5‐fold risk of postoperative mortality among patients with a GI malignancy who are underweight, hypothetically because of nutrient deficiencies 2–5 . Nutrition intervention can help cancer patients maintain body weight and nutrition stores, offering relief from symptoms and improvement in their functional status and quality of life.…”
Section: Introductionmentioning
confidence: 99%